Intelligent profile analysis graduate entrepreneur (iPage) system using business intelligence technology - Abu Bakar, Muhamad Shahbani; Ta'a, Azman; Yahya, Mohd Azlan; Shiratuddin, Norshuhada (2011)
The increase use of information in Malaysia Ministry of Higher Education (MOHE) is resulted from the process of huge and complex data in several stages and at different locations.This situation leads to the difficulties of data management and problematic usage for decision making. Business Intelligence (BI), which is, the process of collecting, analyzing, and transforming data using Data Warehouse (DW) is seen as one of the growing approaches to provide meaningful information.The MOHE is responsible for managing various activities to promote the graduate entrepreneurs to venture into the business and ensure the country has many successful entrepreneurs.Therefore, systematic and accurate information needs to be available for planning, implementation, and monitoring entrepreneurs' performances.This paper proposes the modeling and designing of the graduate entrepreneur profile application called Intelligent Profile Analysis Graduate Entrepreneur (iPAGE) using BI technologies and supporting by a DW approach.Two main methodologies were used namely: Requirements Centric Operational Data Store (ReCODS) and Rapid Application Development (RAD) to develop this system.The iPAGE system was validated and evaluated by iPAGE users and DW experts.It is used to be a guideline for the development of an entrepreneur information system in the future.